Richness Theory: From Value to Action - Mikkelson, Gregory (Les ateliers de l'éthique / The Ethics Forum, 2014)
Richness theory offers a promising axiology. In this paper, I discuss how to translate it into a deontology. To do so, I recruit the concept of moral distance from a recently developed epistemology, and construe it in terms of causal power. Finally, I apply the resulting decision-theoretic framework to the question of how best to avert ecological disaster over the next 36 years and achieve ecological harmony over the next 986.